Manajemen Pelatihan dan Pengembangan Sumber Daya Manusia dalam Meningkatkan Mutu Tenaga Pendidik - Fitrotulizah, Fitrotulizah; Indriyani, Tuti; Zas Pendi, Hamdi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to analyze the management of training and human resource development in improving teacher quality at SMA Negeri 10 Muaro Jambi. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation. Data was analyzed using reduction, display, and conclusion drawing techniques. The findings reveal that training and development programs are implemented through qualification, certification, and Subject Teacher Forum (MGMP), supported by seminars, workshops, and technical training. These programs contribute to enhancing teachers’ pedagogical, professional, social, and personal competencies. The impact is reflected in improved teaching quality and increased stakeholder participation. This study highlights that systematic and sustainable training management is a key strategy in improving educational quality.